El programa para dejar de fumar del Ayuntamiento de Madrid - Moreno, José Javier (Psicooncología, 2006)
Smoking is the most important prevention factor related to disease and death in developed countries. There is scientific evidence of its relation with different types of cancer so all prevention strategies in this disease include tobacco consumption reduction as a principal objective. According to the evidence available, election procedures in smoking treatment are those which use psychological treatment combined or not with pharmacological treatment. This paper presents a theoretical foundation, therapeutic ingredients and a brief sessions guide from the “Programa para Dejar de Fumar del Ayuntamiento de Madrid”, a multicomponent group program carried out in 15 municipal centres “Madrid Salud”. Main results are presented and the paper concludes with an argument in favour of the psychological treatment in front of the prevailing biological reductionism hardly associated with pharmaceutical industry interests.